Comparison of definitive chemoradiotherapy and radiotherapy alone in patients older than 75 years with locally advanced esophageal carcinoma: A retrospective cohort study. Issue 35 (September 2017) - Zhao, Qian; Hu, Guofang; Xiao, Wei; Chen, Yan; Shen, Meng; Tang, Qiang; Ning, Xu
Abstract : Abstract: The aim of this study was to evaluate the efficacy and acute toxicity of definitive chemoradiotherapy (CRT) and radiotherapy (RT) alone as initial treatment in patients aged 75 years and older with locally advanced esophageal squamous cell carcinoma (ESCC) who are not eligible for surgery. Between February 2009 and February 2015, 122 patients older than 75 years with locally advanced ESCC were retrospectively reviewed, in whom 52 patients allocated to the CRT group were treated with at least 2 cycles of platinum and 5-fluorouracil, 70 patients allocated to the RT group were treated with RT alone, all patients were received a total radiation dose of 54–66 Gy, with 1.8 or 2-Gy/fraction. Response rate (RR), progression-free survival (PFS), overall survival (OS), and acute toxicities were compared between the 2 different treatment groups. In the CRT group, the median PFS and OS were 15.3 and 24.6 months, while 10.6 and 19.4 months in the RT group ( P  = .008 and P  = .018). The 1-year survival rates of the 2 groups were 78.8% versus 64.3% ( P  = .081), and the 2-year survival rates were 48.1% and 30.0% ( P  = .042), respectively. The objective RR was 55.8% in the CRT group with 18 complete response (CR) and 18.6% in the RT group with 13 CR. Acute toxicity in the CRT group was higher than in the RT group, especially the grade 3 to 4 acute toxicities. Compared with RT alone, definitive CRT in the treatment of locally advanced ESCC can prolong the survival time in elderly patients. Definitive CRT should be considered the first-treatment choice for elderly patients like the younger patients who are not eligible for surgery.